Moderating Role of Negative Earnings on Firm Size and Corporate Social Responsibility Relationship: Evidence from Listed Firms on Nigeria Stock Exchange - Ndubuisi Odoemelam; Grace Nyereugwu Ofoegbu; Chioma Ojukwu (Universitas Pasundan, 2020)
The fight against coronavirus disease (COVID-19) has called for corporate social responsibility (CSR). Thus, Nigerian businesses, such as in the petroleum and financial industries, have provided hospital donations and 30 million assistance among others to mitigate COVID-19. We investigated the moderating role of negative earnings in firm size–CSR relationship. We used content and logistic panel regression analyses on a sample of 100 firms listed on Nigerian Stock Exchange (NSE). First, we confirmed a positive firm size–CSR relationship (stakeholders’ expectation hypothesis). Second, we found that earnings loss negatively affects stakeholders’ expectation hypothesis. The study suggests that big firms are likely to negatively respond to the clarion call for donations for COVID-19 due to negative earnings. However, our robustness test revealed that old firms positively respond to CSR activities despite earnings loss. Our study results contribute important insights into the current debate concerning the effect of earnings loss on CSR activities. Corporate managers are encouraged to participate in social activities by contributing their resources for human race sustainability and community development, hence enabling stakeholders to highly value their work, money, support, and societal acceptance.